A person-centered perspective on the combined DSM-5 AMPD/ICD-11 personality model: Utility, relationship with the categorical personality disorder model, and capacity to differentiate between levels of identity functioning - Bastiaens, Tim; Bogaerts, Annabel; Luyckx, Koen; Smits, Dirk; Claes, Laurence (Frontiers in Psychiatry, 2022)
Background Both the ICD-11 classification of Personality Disorders and the DSM-5 Alternative Model for Personality Disorders (DSM-5 AMPD) conceptualize personality pathology in a dimensional way, but differ in the way they carve up their respective pathological personality domains. Recently, a combination of ICD-11 and DSM-5 AMPD descriptive pathological personality traits, the Modified Personality Inventory for DSM-5 – Brief Form Plus (PID5BF+M), was developed. The current study We investigated the utility of the additional ANANKASTIA domain (not represented in the DSM-5 AMPD) as well as of the additional PSYCHOTICISM domain (not represented in the ICD-11 model) in the identification of meaningful pathological personality domain clusters based on the PID5BF+M. Next to the classical 2- and 3-cluster solutions, we examined whether the presence of the additional ANANKASTIA domain would also gave rise to a meaningful 4-cluster solution. We then validated these clusters by investigating differences between them in mean DSM-5 Section II cluster A, B, and C personality disorder scores. Finally, we investigated whether cluster membership was able to differentiate between levels of identity functioning, a key feature of personality disorder severity in both the ICD-11 model and the DSM-5 AMPD. Results Cluster analyses on PID5BF+M pathological personality domains (1) revealed meaningful 2-, 3-, and 4-cluster solutions, with the 4-cluster solution explaining the most variance in the clustering variables, (2) allowed to identify a classical Overcontrolled cluster which DSM-5 AMPD PID-5 does not, and (3) demonstrated the utility of representing ANANKASTIA and DISINHIBITON as separate pathological personality domains. PID5BF+M clusters (5) were informative of DSM-5 Section II cluster A, B, and C personality disorder scores and (6) showed different levels of clinical-developmental Identity functioning. Conclusion Current results demonstrate the utility of a combined ICD-11/DSM-5 AMPD view from a person-centered perspective.